Checklist of spiders in Fraser's Hill Wildlife Reserve, Selangor, Malaysia - Chooi, Y. S.; Cheong, Y. L.; Tan, P. E.; Lau, Wei Hong (Department of Wildlife and National Parks (DWNP) Peninsular Malaysia, 2014)
A study of the biodiversity of spider was carried out during Biodiversity Inventory Program at Fraser's Hill Wildlife Reserve, Selangor from 26th July to 2nd August 2009. Samples were collected along selected trails and in the area around the base camp. A total of 249 spiders were collected and 13 families of spiders, namely the Family of Agelenidae, Araneidae, Clubionidae, Lycosidae, Oxyopidae, Pholcidae, Pisauridae, Psechridae, Salticidae, Sparassidae, Tetragnathidae, Theraphosidae, and Theridiidae, were recorded. These spiders were found foraging on trees and the ground. Besides the diverse fauna and flora, Fraser's Hill Wildlife Reserve, Selangor is also a famous host to hairy tropical spiders called tarantulas. Throughout this inventory program, two tarantulas were recorded.